Al-Al‘âb al-Lughawiyah fi Ta’lîm al-Mufradât ‘alâ Asâs al-Madkhal al-Insâniy bi al-Ma’had as-Salafiy - Fadoli, Ach.; Rifki, Mohammad (Jurnal Internasional Pendidikan Bahasa Arab, 2023)
Fun learning will make students happy and not bored in participating in learning, to create this the teacher is required to be creative and innovative and understand the condition of students, one of the learnings that are in great demand by students is game-based learning. the purpose of this study was to analyze the language games applied in vocabulary learning based on a humanistic approach, The research method used is a qualitative descriptive analysis method, with data collection techniques using observation and interviews. The results of this study concluded that the learning process using games language makes students more active and enthusiastic and does not feel bored in mufradat learning besides student-centered learning, so in this case, the teacher is only a facilitator. The language games used are guessing the vocabulary by movement, saying the vocabulary by continuing, singing the vocabulary, and playing how many alif ba' are there. Internal factors that influence the application of language games are student abilities, student desires, and student enthusiasm, while external factors that influence the application of language games are teacher abilities, learning media, and the school environment.